2019
DOI: 10.1590/1980-5373-mr-2019-0251
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic Tests of Alumina-UHMWPE Composites Submitted to Gamma Radiation

Abstract: The energy absorption in ballistic tests of alumina-ultra high molecular weight polyethylene (UHMWPE) composites with 60, 80 and 90 wt% alumina submitted to gamma radiation doses of 25, 50 and 75 kGy was investigated. The ballistic tests were carried out at subsonic speed using a compressed air system. The results showed that the composite with 80% alumina irradiated with 50 kGy yields the best ballistic results. Gel content, Differential scanning calorimetry (DSC) and X-ray diffraction (XRD) results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…The authors observed that fractions of 80 wt% and 85 wt% resulted in the best results of ballistic resistance, in which the penetration of an ammunition caliber .22 LR, was almost null. Figueiredo et al [55] performed ballistic tests with .22 LR ammunition in UHMWPE/Al2O3 composites subjected to gamma radiation at different ratios (0, 25, 50, and 75 kGy). The composites in general showed absorption of ballistic energy around 20% to 30%, results compatible with the present study, however, the addition of 80 wt% Al2O3 and 50 kGy of gamma radiation resulted in the absorption of approximately 65%, resulting in improved ballistic performance.…”
Section: Ballistic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The authors observed that fractions of 80 wt% and 85 wt% resulted in the best results of ballistic resistance, in which the penetration of an ammunition caliber .22 LR, was almost null. Figueiredo et al [55] performed ballistic tests with .22 LR ammunition in UHMWPE/Al2O3 composites subjected to gamma radiation at different ratios (0, 25, 50, and 75 kGy). The composites in general showed absorption of ballistic energy around 20% to 30%, results compatible with the present study, however, the addition of 80 wt% Al2O3 and 50 kGy of gamma radiation resulted in the absorption of approximately 65%, resulting in improved ballistic performance.…”
Section: Ballistic Performancementioning
confidence: 99%
“…Caraschi and Leão [53] found values of hardness around 62, while Koffi et al [54] obtained a hardness of 50.6 Shore D for pure HDPE. With the addition of ceramic reinforcement, the hardness is high, as Al2O3 and SiC have higher hardness than ceramic HDPE, which has a greater hardness than polymeric materials [23,55].…”
Section: Mechanical Characterization Of A00 A40 A50 and A60 Compositesmentioning
confidence: 99%